Youth-led participatory photo mapping to understand urban environments. (November 2017) - Teixeira, Samantha; Gardner, Rachele
Abstract: A large body of research has shown that the neighborhood environment is an important developmental setting for youth. However, there remains a need for deeper qualitative accounts of how youth perceive and experience the neighborhood environment. This study elicited youths' perspectives on their neighborhood environment and its implications for their well-being using Participatory Photo Mapping (PPM), a method that integrates photography, community mapping, and walk-along interviews. Participants ( n  = 6) were black youth age 14–19 recruited from a youth program in Boston, Massachusetts. Participants designed neighborhood tours and through their analysis of the photographs and maps created on those tours, reflected primarily on the stark juxtapositions between lower-income areas of the community and an influx of new construction and neighborhood changes. They also focused on the social and physical environmental features present in lower income areas of the community, honing in on both youth-supporting aspects and those that impede their opportunities such as violence. These findings suggest the importance of understanding youths' perceptions of their neighborhood residential environments and the implications of these perceptions for neighborhood and youth well-being. Graphical abstract: Highlights: This study used a youth-led Participatory Photo Mapping (PPM) research approach. The research involved walk along neighborhood assessments including mapping and photography. Youth noted the juxtaposition of racially segregated areas and unaffordable neighborhood areas. PPM is a strong research and engagement strategy for youth-led, community-focused research.